Laser-Assisted Gingivectomy To Aid The Eruption Of Permanent Maxillary Central Incisors- A Case Report (Journal of Pharmaceutical Negative Results, 2022)
Local factors can lead to the failure of eruption of permanent maxillary central incisors such as early loss of deciduous incisors due totrauma, supernumerary teeth or odontomes, and dilacerated roots. This may lead to loss of space and the presence of thick mucosacovering the permanent incisors that may impede their path of eruption. Delayed permanent teeth can result in irregular dentition,malocclusion, and cystic changes of surrounding bone leading to major adverse effects. This can affect the functional, esthetic, andpsychological well-being of children. Therefore, it becomes necessary to create an opening window to facilitate eruption as soon aspossible.In the present case laser-assisted gingivectomy has been used to aid